Poetics and the Genetics of Creation: The SPHERA Project, or Art as Spiritual Intelligence - Abreu, José Guilherme (Farol, 2026)
This article presents the SPHERA project, which investigates the spiritual dimension of artistic creation as a trans-historical and transcultural foundation of art. It aims to reveal implicit manifestations of spirituality in contemporary art and to establish genealogies connecting works, eras, and cultures. Through a theoretical-interpretative approach and case study analysis, it posits art as a genetic process and a form of spiritual intelligence, redefining public art as a practice of spiritual regeneration and discussing the critical use of artificial intelligence in artistic creation.